Nonlinear Interactive Stories as an Educational Resource - Michal Černý; Kristýna Kalmárová; Monika Martonová; Pavlína Mazáčová; Petr Škyřík; Jan Štěpánek; Jan Vokřál (MDPI AG, 2022)
Working with digitized cultural heritage is an important aspect of education. This article offers research on the interaction of pupils and teachers with digitized cultural heritage processed in the Twine2 environment, focusing on exploring the potential use of digital nonlinear stories in the teaching of humanities in high schools. The aim of this study is to describe the design process that led to the creation of 16 innovative educational resources, and to present the results of their pilot testing and evaluation, which subsequently took place among participating teachers and pupils. For the evaluation, we used a mix of design methods, combining a quantitative and qualitative approach. Both the teachers and the pupils were asked about their experience and takeaways from the interaction with the resources offered. The findings show that presenting educational content in the form of a nonlinear interactive story is a suitable alternative to the traditional frontal educational approach, as both teachers and pupils perceived the resources as intuitive, appealing, and effective in helping to achieve the set educational goals. The study also highlights some key recommendations for future designers of nonlinear interactive stories, which emerged from the respondents' feedback.